The Role of Camp in Promoting the Participants’ Spoken English Expression - jalaluddin Jalaluddin (IJEE (Indonesian Journal of English Education), 2015)
The study investigated the topics of participants’ spoken expressionin an English camp and how the topics were discussed.A case study was applied as the research design. Data were gained from focus-group interviews, observation, and questionnaire. The results showed that the participants talked about various topics, which could be categorized into two types i.e. guided topics and situational topics. Guided topics were discussed by the participants in guided conditions. On the other hand, situational topics appeared naturally with respect to the situation. The data also indicated that the activeness and confidence of the participants to talk in English gradually increasedduring the English camp. The findings suggested that English campsbeheld regularly as they can boost the participants’ English speaking skill.